BNN-1, 3-dipoles: isolation and intramolecular cycloaddition with unactivated arenes. Issue 27 (25th June 2020) - Guo, Rui; Jiang, Jingxing; Hu, Chenyang; Liu, Liu Leo; Cui, Ping; Zhao, Meihua; Ke, Zhuofeng; Tung, Chen-Ho; Kong, Lingbing
Abstract : The mono-base-coordinated 1, 2-diboranylidenehydrazine derivatives exhibiting the BNN-1, 3-dipolar reactivity toward unactivated arenes and CO2 are reported. Abstract : The mono-base-stabilized 1, 2-diboranylidenehydrazine derivatives featuring a 1, 3-dipolar BNN skeleton are obtained by dehydrobromination of [ArB(Br)NH]2 (Ar = 2, 6-diphenylphenyl (Dpp), Ar = 2, 6-bis(2, 4, 6-trimethylphenyl)phenyl (Dmp) or Ar = 2, 4, 6-tri- tert -butylphenyl (Mes*)) with N-heterocyclic carbenes (NHCs). Depending on the Ar substituents, such species can be isolated as a crystalline solid (Ar = Mes*) or generated as reactive intermediates undergoing spontaneous intramolecular aminoboration of the proximal arene rings via [3 + 2] cycloaddition (Ar = Dpp or Dmp). The latter reactions showcase the 1, 3-dipolar reactivity toward unactivated arenes at ambient temperature. In addition, double cycloaddition of the isolable BNN species with two CO2 molecules affords a bicyclic species consisting of two fused five-membered BN2 CO rings. The electronic structures of these BNN species and the mechanisms of these cascade reactions are interrogated through density functional theory (DFT) calculations.